ANALISIS TOKOH KOYAL DALAM MEGA,MEGA KARYA ARIFIN C. NOER: KONSEP SUBJEK SLAVOJ ŽIŽEK - Elyandra Widhart (Jurnal Pendidikan Seni dan Industri Kreatif, 2021)
Slavoj Žižek describes concept of the subject based on Lacan’s psychoanalysis concept. Concept of the subject is divided into three, namely The Real, The Imaginary, and The Symbolic. The three subject concepts are the stages experienced by human beings in their existence. The current study attempts to analyze descriptively the character of Koyal in Arifin C. Noer's “Mega,Mega” employing the concept of Slavoj Žižek's subject. The purpose of analysis is to disclose the existence of Koyal as a paradoxical subject other than the dimensional side. The analysis brings about the conclusions that Koyal is present as a character with high level imagination. He is often considered abnormal by people around him like Hamung, Panut, Retno and Tukijan. Koyal apparently has experienced positions as the Real subject, The Imaginary, and The Symbolic along the plot of the play. However, Koyal has finally failed to reach the Real eventhough he has been reminded through the presence of another subject as The Imaginary. Subsequently, Koyal’s efforts to reach the Symbolic by setting up his existence in a certain position in the middle of the community has also failed.